Heat Attainment and Retention in Surfers with and without a Land-Based Warm-Up and Accompanying Passive Heat Retention - Christian J. Cook; Benjamin G. Serpell; Lauren J. Hanna; Aaron Fox; Phillip J. Fourie (MDPI AG, 2024)
Surfing is a growing, high-participation recreational and competitive activity. It is relatively unique, being performed on, in, and through water with a range of temperatures. In other sports, warm-up and heat retention have proved useful at augmenting performance and ameliorating injury risk. Little work has been carried out examining this in surfing. The purpose of this work was to measure thermal profiles in surfers with and without warm-up and passive heat retention, and secondarily to assess any potential influence on free surfing. A repeated measures pre- and post- design was adopted whereby participants surfed in an artificial wave pool following an active warm-up combined with passive heat retention (experimental condition) and after no warm-up (control). Core body temperature was measured both occasions. Our results showed increases in core body temperature were greater for the experimental condition versus control (p = 0.006), and a time effect exists (p < 0.001)-in particular, a warm-up effect in the water itself was shown in both groups, possibly due to further activity (e.g., paddling) and wetsuit properties. Finally, performance trended to being superior following warm-up. We conclude that body warmth in surfers may be facilitated by an active warm-up and passive heat retention. In free surfing, this is associated with a trend towards better performance; it may also reduce injury risk.